Incidence and prevalence levels of three aphid-transmitted viruses in crucifer crops in China - Xiao-yan ZHANG; Yan-mei PENG; Hai-ying XIANG; Ying WANG; Da-wei LI; Jia-lin YU; Cheng-gui HAN (Journal of Integrative Agriculture)
Poleroviruses, which are distributed worldwide, infect many crops of economic importance and cause severe plant diseases. Brassica yellows virus (BrYV), which has three genotypes, A, B, and C, is a newly identified polerovirus infecting crucifer crops in China, but its distribution is still unclear. Here, we report the distribution and prevalence levels of the three BrYV genotypes in crucifer crops in China. A total of 570 crucifer leaf samples randomly collected from 22 provinces, four ethnic minority autonomous regions, and three municipalities in China were tested for BrYV. RT-PCR detection showed that 97 of the field samples were positive for BrYV, and the average incidence of BrYV was 17.0%. The virus was detected in 22 provinces, with high incidences in north, northwest, and northeast China. The multiplex RT-PCR amplification of the three BrYV genotypes revealed that both single and mixed infections occurred. Among the BrYV infections, 38.1% were mix-infected by more than two viral genotypes, and 8.2% samples were mix-infected by three viral genotypes. Our findings indicated a widespread prevalence of BrYV in China, and BrYV mixed infections with Turnip mosaic virus and Cucumber mosaic virus in crucifer crops are common. This study is the first large-scale survey of BrYV in crucifer crops in China. The information generated in this investigation will contribute to the national prevention and control of viral diseases.